The Progress and Perspective of Organic Molecules With Switchable Circularly Polarized Luminescence - Gao, Yang; Ren, Can; Lin, Xiaodong; He, Tingchao (Frontiers in Chemistry, 2020)
Circularly polarized luminescence (CPL) has been under intense research for future applications in high resolution 3D display, smart sensors and information technologies. Different types of CPL materials have been developed, but neither the handedness nor the asymmetrical luminescence degree can be inferred from the material composition or the components. CPL materials with switchable handedness or emission wavelength play an important role, reducing the need for repetitive bottom-up synthesis. Herein will be presented, switchable CPL behaviors towards multiple reported stimuli, including light irradiation, host-guest interaction, metal ions, pH, solvent, temperature, etc. This summary and discussion of the effective stimuli is aimed to promote rational future material exploration and boost related multidisciplinary applications.